Enacting criticality and care - Agherdien, Najma (Critical Studies in Teaching and Learning, 2023)
Thisarticleprovides an account of onehigher education teacher’sviews on the notions of criticality and critiquewithin the context of continuous professional learning spaces for academicsand in which the Scholarship of Teaching and Learning(SoTL)is central.Ipresent an account of enactingSoTL practices through criticality and(with)care. Included is an account of SoTL engagements with academics,a processthat takes time, courage, patience,and hope.The argument that Imake is that withholding critical care–whichincludes attentiveness, responsibility, competence,and responsiveness -is part of injustice. Hence, contestation, criticality,and critique with care must remain key SoTL activities. A twin argument is that (self) criticality is a precursor to critiquing others. The article concludeswith implications of enacting criticality with care, in SoTL and beyond.